Strategic management and student satisfaction at San Carlos Private University. Puno Peru 2019 - Pérez Pérez, Juan; Rios Rios, Segundo Waldemar; Torres Chumbiauca, Lesli Elilzabeth; Wu Matta, Julio; Olivares Zegarra, Soledad del Rosario; Ochoa Paredes, Fernando (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The article was prepared in order to establish how strategic administration influences student satisfaction at the San Carlos Private University. Ilave. 2019. The reason for carrying out this study was to contribute to the university institution for a better institutional functioning. It was of an explanatory type, its design was non-experimental, cross-sectional, which accumulated the data in a delimited time, it was tended by applying the instruments that are the questionnaires to the students of the university. There was a populatios of 587 students and a sample 238 university students from profesional schools and from various cycles. It was concluded that strategic management influences the satisfaction of students at the San Carlos Private  University demonstrating 75,1 % in the verification of the hypothesis.